Immunohistochemical correlation between microvessel density and lymphoid infiltrate in radicular cysts. (13th July 2012) - Zizzi, A; Aspriello, SD; Ferrante, L; Stramazzotti, D; Colella, G; Balercia, P; Lo Muzio, L; Piemontese, M; Goteri, G; Rubini, C
<x xml:space="preserve">Abstract</x> Oral Diseases (2012) 19, 92–99 Objective: Radicular cysts occur as a result of the immunological response to continuous antigenic stimulation from root canals. We correlated the immunophenotypical composition of the lymphoid infiltrate to the microvessel density expressed by the count of CD34 reactive endothelial cells in radicular cysts. Subjects and methods: Thirty‐four cases of radicular cysts were evaluated by immunohistochemistry, using antibodies against B‐ and T‐cell antigens (CD20, CD3, CD4, CD8) and against the endothelial cell marker CD34. Statistical analysis was performed. Results: In the epithelium, we observed a low amount of lymphoid infiltrate in all 34 radicular cysts, and a strong significant negative correlation between T and B lymphocytes and between T‐helper and T‐cytotoxic/suppressor lymphocytes. In the cyst capsule, we observed a significant positive correlation between B and T lymphocytes, B and T‐cytotoxic/suppressor lymphocytes, T and T‐helper lymphocytes and between the number of CD34+ blood vessels and T and T‐helper lymphocytes, respectively. We observed a statistically significant correlation between percentage of CD34+ vessels and inflammatory infiltrate grade. Conclusions: Both humoral and cellular immune reactions and neovascularization are likely to occur in the complex events of tissue destruction. The inflammatory infiltrate has an important role in neoangiogenesis and consequently in radicular cysts development and growth.